Cattle owners' awareness of bovine tuberculosis in high and low prevalence settings of the wildlife-livestock interface areas in Zambia - Munyeme, Musso; Muma, John B.; Munang'andu, Hetron M.; Kankya, Clovice; Skjerve, Eystein; Tryland, Morten (BMC Veterinary Research, 2010)
Awareness of bovine tuberculosis (BTB) by cattle owners is of extreme importance to policy makers when considering mitigation. However, to our knowledge, little is known on cattle owners' awareness of BTB in Zambia. Similarly, such knowledge is uncommon within and outside Africa. The current study investigates the epidemiological characteristics of BTB in Zambian cattle in relation to awareness by cattle owners in high and low cattle BTB prevalence settings. A cross sectional study was designed and data was gathered based on 106 cattle owners and cattle herds; subjected to an interviewer-administered questionnaire and comparative intradermal tuberculin test using a cut-off for positivity of 4 mm, respectively. Results: Reported levels of cattle and wildlife contact by respondents was at 40%, 58.2% and 1.8%, were relatively proportional to herd level prevalence of cattle BTB at 64.8%, 58.1% and 5.9% in Blue lagoon, Lochinvar and Kazungula respectively. Although 42/106 (39.6%) of cattle owners had heard of BTB, only 3 (7%) had an idea on how the disease was spread. Cattle contact with wildlife was associated with high levels of awareness by cattle owners (χ2 = 43.5, df = 2, P < 0.001). Awareness of BTB in low prevalence settings was lower compared to high prevalence settings. Conclusions: Our study has revealed low levels of awareness among cattle owners on BTB. These results could be useful for policy makers when planning mitigation measures to consider awareness levels by cattle owners for effective implementation. Such information is useful for determining sensitisation programs for cattle owners before mitigation. These results further provide useful insights that disease control is a multi-factorial process with cattle owners as an integral part that can support policy implementation.
Keywords: Cattle; Bovine tuberculosis; Wildlife-livestock; Zambia